Healthcare workers' compliance with COVID-19 preventive measures, and associated factors, in Ethiopia: A systematic review and meta-analysis. Issue 8 (5th August 2022) - Zenbaba, Demisu; Sahiledengle, Biniyam; Beressa, Girma; Desta, Fikreab; Atlaw, Daniel; Bogale, Daniel; Chattu, Vijay Kumar
Abstract : Objective: Compliance with COVID-19 prevention measures limits infection occurrence and spread in healthcare settings. According to research conducted in Ethiopia, compliance with COVID-19 preventative strategies is inconsistent among healthcare providers. This systematic review and meta-analysis aimed to estimate the national pooled proportion of healthcare workers (HCWs) who adhere to COVID-19 preventive measures and associated factors with good compliance. Design: A systematic review and meta-analysis of all identified studies with cross-sectional study design. Data sources: A comprehensive search was conducted in PubMed/MEDLINE, POPLINE, HINARI, Science Direct, Cochrane Library databases and Google Scholar search engines from January 2020 to September 2021. Data extraction and synthesis: This review included all observational studies conducted in Ethiopia that reported the proportion of compliance with COVID-19 preventive measures and associated factors among HCWs. Two independent authors assessed the methodological quality of studies using Joanna Briggs Institute's meta-analysis of statistical assessment and review instrument. The effect estimates for pooled proportion and pooled OR (POR) were determined. Results: From retrieved 611 original studies, 21 studies were included in the meta-analysis with a total of n=7933 HCWs. The pooled proportion of good compliance with COVID-19 preventive measures among HCWs was 49.7% (95% CI: 42.3% to 57.1%). Being male (POR=2.21, 95% CI: 1.52 to 3.21), service years (>3 years) (POR=2.65, 95% CI: 1.94 to 3.64), training (POR=2.30, 95% CI: 1.78 to 2.98), positive attitude (POR=3.14, 95% CI: 1.66 to 5.94) and good knowledge (POR=2.36, 95% CI: 1.92 to 2.89) were factors significantly associated with good compliance towards COVID-19 preventive measures. Conclusion: Our study indicated that approximately one in every two HCWs had good compliance with COVID-19 preventive measures. There must be more emphasis on providing further training sessions for the HCWs to improve their compliance with COVID-19 preventative measures.